Coenura Bigot as a valid genus: A molecular and morphological phylogenetic analysis of Pelecorhynchus Macquart sensu lato (Diptera: Pelecorhynchidae) - González, Christian R.; Saldarriaga-Cordoba, Mónica; Aguilera, Omayra; Miranda-Esquivel, Daniel Rafael (Zootaxa, 2023)
The phylogeny of the genus Pelecorhynchus Macquart (Diptera: Pelecorhynchidae) was analyzed using three genes, cytochrome oxidase I, 28S ribosomal DNA, and CAD5, with 112 morphological characteristics. A total of 59 specimens (13 outgroups and 46 ingroups) were included in the analysis. The monophyly of Pelecorhynchidae was recovered under all analyses, with Glutops Burgess as the sister group of Pelecorhynchus s.l., while Pseudoerinna jonesi (Cresson) was the sister group. Within “Pelecorhynchus” there are three main clades with unresolved affinities. Clade I was formed by P. personatus (Walker), P. vulpes (Macquart), P. penai Pechuman and P. kroeberi (Lindner), a well-supported clade. Clade II corresponds to the set of species of “Chilean Pelecorhynchus”, conformed to P. biguttatus (Philippi), P. toltensis Llanos & González, P. elegans (Philippi), P. xanthopleura (Philippi), P. hualqui Llanos & González, and P. longicauda (Bigot), a well-supported clade. Clade III is represented exclusively by P. fulvus Ricardo, which has an exclusively Australian distribution. The monophyly of P. fulvus and its nomenclature remain an open question, as only a single species of this taxon was included. Our study demonstrated that the concept of Pelecorhynchus should be revisited. Therefore, we restore Coenura Bigot, 1857 to generic status for part of the southern South American species of “Pelecorhynchus” conformed by the species C. biguttata, C. elegans, C. hualqui, C. longicauda, C. toltensis, and C. xanthopleura which are monophyletic, supported by molecular and morphological data, and consistent with a Chilean distribution.